1989
DOI: 10.1007/bf01311360
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of passive immunity against hantavirus infection in rats

Abstract: The protective effects of passively administered antibodies against hantavirus infection were studied in newborn rats. Death as well as infection were completely prevented from intraperitoneal challenge of strain SR-11 (SR) (2 x 10(3) FFU, 10(2.1) LD50), in newborn rats which received 0.1 ml of anti-SR rat serum (neutralizing antibody titer, 1:640) 4 hr before the virus challenge. In these rats, no virus was detected in the peritoneal macrophages, lung, kidney, and brain. The immune serum infusion before the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Reports that high NAb titers in patients admitted to hospitals correlated with a favorable clinical course suggested that NAbs might ameliorate disease, and therefore, that immunotherapy could be a viable treatment option for persons exposed to HPS viruses (5). For HFRS-associated hantaviruses, passive transfer of infected-rat immune serum or mouse MAbs conferred protection against infection in hamsters or neurologic disease in newborn rats or suckling mice (2,17,28,31). For HPS hantaviruses, there have been no reports of the passive transfer of protective immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Reports that high NAb titers in patients admitted to hospitals correlated with a favorable clinical course suggested that NAbs might ameliorate disease, and therefore, that immunotherapy could be a viable treatment option for persons exposed to HPS viruses (5). For HFRS-associated hantaviruses, passive transfer of infected-rat immune serum or mouse MAbs conferred protection against infection in hamsters or neurologic disease in newborn rats or suckling mice (2,17,28,31). For HPS hantaviruses, there have been no reports of the passive transfer of protective immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Passive transfer of neutralizing antibodies can protect susceptible animals from hantavirus infection (8,(53)(54)(55)62), and there is a report that convalescent-human sera can afford some protection in acutely infected individuals (58). Thus, characterizing the structures and functions of these proteins will be important for understanding CCHFV tropism and pathogenesis as well as for vaccine development.…”
mentioning
confidence: 99%
“…The large (L) segment encodes the RNA-dependent RNA polymerase the small (S) segment encodes the nucleocapsid protein (N) and the medium (M) segment encodes a polypeptide that is cotranslationally cleaved to yield two membrane-associated glycoproteins, G1 and G2. G1 and G2 form oligomers that comprise the surface morphologic units of the virion and are the targets of neutralizing antibodies (1,9,29). Passive transfer of neutralizing antibodies protects newborn rats (29), suckling mice (2), or hamsters (24) against infection.…”
mentioning
confidence: 99%
“…G1 and G2 form oligomers that comprise the surface morphologic units of the virion and are the targets of neutralizing antibodies (1,9,29). Passive transfer of neutralizing antibodies protects newborn rats (29), suckling mice (2), or hamsters (24) against infection. N-specific antibodies are neither neutralizing nor protective.…”
mentioning
confidence: 99%